Exuberant case of verrucous cutaneous leishmaniasis - Jana Regis Novaes; Luise Ribeiro Daltro; Thiago Amparo Ferreira; Paulo Roberto Lima Machado (Sociedade Brasileira de Dermatologia, 2022)
Abstract Cutaneous leishmaniasis represents a public health problem that affects 85 countries. It is an endemic disease in Brazil, having an important socioeconomic impact. An exuberant case of cutaneous leishmaniasis is reported herein. A 28-year-old male patient with Down syndrome had had verrucous plaques on the back for over a year, with progressive growth. PCR of a lesion sample was positive for Leishmania braziliensis. The patient's condition was classified as atypical cutaneous leishmaniasis. He was successfully treated with amphotericin B and miltefosine. The treatment remains a challenge, given the toxicity and low cure rate of the currently recommended drugs.